Problem-based Learning Revisited, introduction of Active and Self-directed Learning to reduce fatigue among students - Czabanowska, Katarzyna; Moust, Jos; Meijer, André; Schröder-Bäck, Peter; Roebertsen, Herma (Journal of University Teaching and Learning Practice, 2012)
Despite several years of successfully applying problem-based learning at Maastricht University, the Faculty of Medicine observed a slow erosion of problem-based practices and “PBL fatigue” among themselves and students. In response to this fatigue and new research into the development of the young adult brain, Active Self-Directed Learning was introduced through the new bachelor of European Public Health programme in an effort to re-energise the classical PBL model and reduce or eliminate erosion. ASDL is split into a four part learning cycle: 1) sensitisation, 2) exploration, 3) integration, and 4) application. The cycle supports problem-based learning and the developing minds of students through the integration of information, critical thinking and self-evaluation, while also teaching self-responsibility and team management skills. When applied as part of a problem-based learning curriculum, ASDL at Maastricht University helped reduce PBL fatigue and re-energised students’ interest in PBL within the first EPH cohort (2006-2009) according to survey feedback obtained after the 5th semester. The positive student response was tempered by recommendations on how to continue improving the ASDL model.